EFFET D’UN TRAITEMENT THERMIQUE PRECOCE D’UNE SEMAINE A TEMPERATURE DECROISSANTE SUR L’EVOLUTION DU POIDS VIF DU POULET DE CHAIR ELEVE EN CLIMAT CHAUD - Zineb, Bengharbi; Said, Dahmouni; Aziz, Mouats; Miloud, Halbouche (European Scientific Journal, ESJ, 2014)
This work was conducted to study the effect of early age conditioningof broilers as a mean against high chronic ambient temperatures and theirbad effects on zootechnical performances and the economic losses theygenerate.400 one day-old broiler Hubbard chicks were randomly assigned tofour treatments (n = 100): (T) control (normally raised), (Aa) and (Ab) earlyage thermal conditioning (exposed to temperature of 39±1°C for 24 h at 3rdday of age and at 5th day of age respectively, and (Ac) chronic stress(exposed to gradually decreasing temperatures from 40°C to 34°C from dayone till day 8 of age). During growth and finishing periods, experimentalanimals were raised in thermal ambiance of 28±1°C.Chicks‘ daily growth evolution during the first 8 days of life was significantin groups T and Ac, but was not significant in Aa and Ab groups which wasprobably due to disturbed growth caused by the heat treatment. However, itsweekly evolution Aa and Ab showed a compensative growth since the 4thweek revealed by body weights of 1625g±26.97 and 1736g±26.71respectively. A highly compensation difference (p˂0.05), was noticed at theend of the 7th week in Ab group subjects (3622.2g±42.15) compared to2681g±85.95, 2680g±5513 and 2424g±66.45 of T, Aa and Ac respectively.In conclusion, early age thermal conditioning of broilers at 39±1°C for 24 hduring the 5th day of age enables to lute against decreased final bodyweights caused by elevated chronic ambient temperatures.